The Competency Of The School Head In Improving Teacher Performance At SMP Islam Plus Al Fatih Medan - Fitri, Adelia; Anggraini , Anggi; Damanik, Aulia Sari; Azrohid, Fauzan; Tanjung, Laila Ali; Parlindungan, Soleh (Jurnal Pendidikan Indonesia, 2023)
This study aims to identify planning, implementing, assessing, and improving the performance of primary school teachers. This study used qualitative methodology. In this study, data collection from various sources, backgrounds, and methods was carried out through literature studies. The findings of this study showed that school principals were able to improve the performance of primary school teachers. To that end, the headmaster must create an annual school work plan (CTR) that addresses eight educational standards, provides SKP (employee performance target) criteria at the beginning of the year as a guideline for teacher assessment by the principal, and implements DP3, on Teacher behavior assessment, in academic settings such as education during evaluation. The Principal oversees teacher education (class visit techniques, one-on-one conversations, and group discussions), as well as the efforts made by Establishing effective communication with all teachers will improve performance in creating a successful workplace culture.